PENGARUH MODEL CIRCUIT LEARNING TERHADAP KEMAMPUAN MENULIS PUISI DITINJAU DARI KREATIVITAS SISWA SEKOLAH DASAR - Akhyar, Fitria; Sugianto, Sugianto; Erni, Erni (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
The purpose of this study was to obtain empirical data on the effectiveness of the learning model of circuit learning on the ability to write poetry of students in terms of the creativity of fifth grade students at SDN 1 Gunung Terang Bandarlampung. The research method used is experiment. This research was conducted at SDN 1 Gunung Terang, Bandarlampung. The research sample was taken using multistage randomg sampling technique. Data analysis techniques in this study include: (1) descriptive data analysis; (2) Test requirements; (3) inferential data analysis. The data analysis technique used is the one-way ANAVA technique. The results showed that from the Anova one-way calculation, the significance value (Sig.) Of 0.000 <0.05 was known. So, it can be concluded that the average value of writing poetry from the three categories of creativity (high-medium-low) is "significantly different".